2002
DOI: 10.1002/jcp.10166
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog is involved in osteoblast differentiation by cooperating with BMP‐2

Abstract: The roles of Sonic hedgehog (Shh) and Bone morphogenetic protein-2 (Bmp-2) in osteoblast differentiation were investigated using in vitro cell systems. Recombinant amino-terminal portion of SHH (rSHH-N) dose dependently stimulated ALP activity in C3H10T1/2 and MC3T3-E1 cells. rSHH-N induced expression of Osteocalcin mRNA in C3H10T1/2 cells. A soluble form of the receptor for type IA BMP receptor antagonized rSHH-N-induced ALP activity in C3H10T1/2 and MC3T3-E1 cells, indicating that BMPs are involved in SHH-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 40 publications
(38 reference statements)
4
63
0
Order By: Relevance
“…These studies suggested that Ihh, and not Shh, is the central determinant of intramembranous calvarial ossification. However, it is curious that Shh has been well known to be a potent osteogenic factor in various cell types and model systems, both in vitro and in vivo (Jemtland et al, 2003;Nakamura et al, 1997;Yuasa et al, 2002). Keeping this in mind, we cannot exclude the possibility that Shh, to some extent, ameliorates the Ihh null mouse calvarial phenotype.…”
Section: Relationship Between Ihh and Shh In Cranial Bonementioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggested that Ihh, and not Shh, is the central determinant of intramembranous calvarial ossification. However, it is curious that Shh has been well known to be a potent osteogenic factor in various cell types and model systems, both in vitro and in vivo (Jemtland et al, 2003;Nakamura et al, 1997;Yuasa et al, 2002). Keeping this in mind, we cannot exclude the possibility that Shh, to some extent, ameliorates the Ihh null mouse calvarial phenotype.…”
Section: Relationship Between Ihh and Shh In Cranial Bonementioning
confidence: 99%
“…Although Hedgehog signaling (mediated by either Indian or Sonic) has been observed to enhance the osteogenic differentiation in numerous bone forming cells in vitro (Ho et al, 2007;James et al, 2010;Jemtland et al, 2003;Levi et al, 2011;Nakamura et al, 1997;Spinella-Jaegle et al, 2001;Yuasa et al, 2002;van der Horst et al, 2003;Wu et al, 2004;Zunich et al, 2009), the precise effects of Ihh in calvarial ossification have not been yet defined. Toward this end, Abzhanov et al studied Ihh misexpression in chick and mouse calvaria.…”
Section: Defining the Etiopathogenesis Of The Ihh 2/2 Calvarial Phenomentioning
confidence: 99%
“…SHH initiates the expression of Bmp2 in the mesoderm (31). During osteogenesis and chondrogenesis, SHH alters the response of cells to BMPs (32,33). SHH has been reported to facilitate BMP-2-mediated Smad1 activation in osteoblasts (34).…”
Section: Role Of Prostate Cancer Cells On the Differentiation Of Bonementioning
confidence: 99%
“…Thus, improving the efficacy of BMP treatment and searching for alternative osteogenic factors or genes have become the most important topics in bone regeneration therapy. Cooperation of two or multiple pathways to promote bone formation in a tissue-engineering application has not yet been fully explored and is fertile ground for future investigation [58,99].…”
Section: Design Considerations For Functional Tissue Engineering Of Pmentioning
confidence: 99%